A new rapid method for direct antimicrobial susceptibility testing of bacteria from positive blood cultures. Issue 1 (December 2016) - Barnini, Simona; Brucculeri, Veronica; Morici, Paola; Ghelardi, Emilia; Florio, Walter; Lupetti, Antonella
Abstract Background Rapid identification and antimicrobial susceptibility testing (AST) of the causative agent(s) of bloodstream infections can lead to prompt appropriate antimicrobial therapy. To shorten species identification, in this study bacteria were recovered from monomicrobial blood cultures by serum separator tubes and spotted onto the target plate for direct MALDI-TOF MS identification. Proper antibiotics were selected for direct AST based on species identification. In order to obtain rapid AST results, bacteria were recovered from positive blood cultures by two different protocols: by serum separator tubes (further referred to as PR1), or after a short-term subculture in liquid medium (further referred to as PR2). The results were compared with those obtained by the method currently used in our laboratory consisting in identification by MALDI-TOF and AST by Vitek 2 or Sensititre on isolated colonies. Results The direct MALDI-TOF method concordantly identified with the current method 97.5 % of the Gram-negative bacteria and 96.1 % of the Gram-positive cocci contained in monomicrobial blood cultures. The direct AST by PR1 and PR2 for all isolate/antimicrobial agent combinations was concordant/correct with the current method for 87.8 and 90.5 % of Gram-negative bacteria and for 93.1 and 93.8 % of Gram-positive cocci, respectively. In particular, 100 % categorical agreement was found with levofloxacin for Enterobacteriaceae by both PR1 and PR2, and 99.0 and 100 % categorical agreement was observed with linezolid for Gram-positive cocci by PR1 and PR2, respectively. There was no significant difference in accuracy between PR1 and PR2 for Gram-negative bacteria and Gram-positive cocci. Conclusions This newly described method seems promising for providing accurate AST results. Most importantly, these results would be available in a few hours from blood culture positivity, which would help clinicians to promptly confirm or streamline an effective antibiotic therapy in patients with bloodstream infections.